Popularizing the historical and cultural heritage of the Kiev-Pechersk National Historical and Cultural Reserve (based on the experience of implementing the program „Museum entertainment for children and adults”) - Topylko, Oleh (Granice tolerancji w sztuce i w wychowaniu, 2020)
The author of the article refers to the achievements of museum pedagogy, emphasizing the importance of interactive forms of work. It refers in the text to educational and cultural projects promoted in the Kiev-Pechersk National Historical and Cultural Reserve and describes the methodological solutions proposed in the museum (e.g. quizzes, cognitive games, staging, theatrical reproductions of events). Analyzing the contribution of interactive forms to making the museum offer more attractive, the author notices many advantages of using modern methods in popularizing historical and cultural heritage.